Lie to me [large type] - Ellison, J. T. (Thorndike Press, a part of Gale, a Cengage Company, 2017)
"Sutton and Ethan Montclair's idyllic life is not as it appears. They seem made for each other, but the truth is ugly. Consumed by professional and personal betrayals and financial woes, the two both love and hate each other. As tensions mount, Sutton disappears, leaving behind a note saying not to look for her"--Dust jacket flap.